Online Automated Network Backup For Archive File To Local Clients - MANJUNATHA B A (2008)
INTERNAL GUIDE : Sridevi N . EXTERNAL GUIDE : Ranjib USN No : 1MJ07SCS07 CARRIED OUT AT : P B H EMind Information Technologies (P) Ltd Bangalore-560 038 ACC NO : PC74
Keywords: M.Tech Computer Science